PEDAGOGICAL CONDITIONS FOR THE DEVELOPMENT OF COGNITIVE INDEPENDENCE FOR HUMANITARIAN STUDIES IN THE PROCESS OF MATHEMATICAL EDUCATION - Vasilievna Ivanova, Augustina; Innokentievich Golikov, Alexei; Gavrilovna Skryabina, Alevtina; Vasilievna Gogoleva, Irina; Agitovna Darbasova, Laura (Gênero & Direito, 2020)
: The relevance of this study is determined by the modern requirements related to both the structure of the learning process and the results of training and educating the younger generation in the context of globalization and informatization of a rapidly changing society. This manuscript is focused on discussing the development of cognitive independence, through humanities classes, among students studying mathematics at a basic level of the new federal state educational standard. The purpose is to find pedagogical conditions that contribute to the development of the cognitive independence of students in humanities while studying mathematics at a basic level. The authors provide a logical and didactic analysis of the existing basic-level mathematics textbooks and describe the features of the students in the humanitarian classes. The authors substantiate the pedagogical conditions required for the development of cognitive independence among these students: enrichment of the content of the humanitarian subject areas with an educational and methodological complex aimed at developing cognitive independence; the involvement of students in the humanitarian classes to develop an independent cognitive process under the condition of using the educational information environment. These conditions are said to activate mental activity, contributing to the development of cognitive independence in the study of mathematics. The authors describe pedagogical approaches (activity-oriented, personality-oriented, information-communicative, and competency-based approaches) that contribute to the development of students’ cognitive independence. The authors present the research methods (assessment of motivation for learning activities, observation of the manifestation of students’ strength-will during tasks, the quality of knowledge in mathematics). The authors conducted an experiment on the implementation of sound pedagogical conditions, the results of which are described in this manuscript. The introduction of the proposed pedagogical conditions into the educational process is of practical importance and is expected to contribute to the effective development of cognitive independence, through humanitarian classes, among students studying mathematics